Overcriminalization Based on Foreign Law: How the Lacey Act Incorporates Foreign Law to Overcriminalize Importers and Users of Timber Products - Matthew S. White (Washington University Global Studies Law Review, 2013)
After assessing the law, this Note argues that the application of foreign law to companies using timber products is an example of vast over-criminalization that should be addressed through judicial reinterpretation of case law that had developed under the Lacey Act (“the Act”) prior to the inclusion of timber products, through rewriting the legislation to address the pertinent issues, or some combination thereof. Part I explores the history and expansion of the Act, including discussion of case law that developed before the Act was amended in 2008 to extend its applicability to timber and wood products. Part II argues that the timber and wood products markets are significantly different from the markets against which the Act has historically applied and that the law surrounding the Act needs to be reconsidered in light of these differences. Part III discusses various options for resolving these issues and ultimately argues that a repeal of the 2008 Amendments or other legislative modification of the law is warranted.
Keywords: foreign law; Lacey Act; timber; wood products; overcriminalization